Principes d'intervention en counseling de carrière pour les jeunes femmes - Spain, Armelle; Hamel, Gary H. (Canadian Journal of Counselling and Psychotherapy, 1993)
In search of an enlightened point of view facilitating the understanding of women's career development, this project takes its origin from a theoretical perspective that links together identity development, vocational development and the relational component of identity. Summarized in this paper, the findings of a qualitative study questioning young women directly on these issues, have led researchers to specific goals and guidelines for an intervention meeting female needs. Essentially, the relational component of identity appears as a fundamental concern when the vocational development of women is considered.